Economic appraisal of transport projects : a manual with case studies - Adler, Hans A. (Baltimore : Published for the World Bank [by] Johns Hopkins University Press, 1987)
An introduction to the application of cost-benefit analysis to transportation investments in developing countries
Includes Bibliographical references (p. 208-230) and index.
eng
Keywords: Transportation; Transportation